'The art of kindergarten drop off': how young Norwegian-Somali parents perform ethnicity to avoid reports to Child Welfare Services. Issue 3 (4th May 2021) - Handulle, Ayan; Vassenden, Anders
ABSTRACT: This paper departs from an ethnography of Somali parents in Oslo, Norway, which examined perceptions of the Child Welfare Services (CWS). We explore how young second-generation parents portray middle class identities when they interact with school and kindergarten personnel. These are institutions under legal obligation to report to the CWS if they suspect neglect of children. Drawing on Goffman, we analyse how parents conduct and meticulously prepare for encounters with school and kindergarten personnel. These preparations pertain to countering ethnic stigma and avoiding racial scrutiny, in large part to avoid referrals to the CWS. Our paper makes the following contributions. In the study of child welfare and ethnicity, we stress the importance of visible ethnicity – or 'race' – and show how scepticism of CWS derives from suspicions of racial prejudice; strained relations between migrants and the CWS extend far beyond interactions between caseworkers and clients as they also stem from interactions with adjacent institutions. Regarding the study of ethnic relations, we argue that understanding performance of ethnicity requires inclusion of institutional contexts, such as the schools, kindergartens and the CWS.